Multivariate Optimization of Binary Solvent Microextraction for the Simultaneous Determination of Endocrine Disruptive Phenolic Compounds and Organochlorine Pesticides in Wastewater and Sludge Samples by GC-MS - Chormey, Dotse Selali; Firat, Merve; Bakirdere, Sezgin (SPRINGER INTERNATIONAL PUBLISHING AG, 2018)
This study presents the development of a sensitive and accurate dispersive liquid-liquid microextraction method using binary solvents for the simultaneous determination of endocrine disruptive compounds by GC-MS. Optimum binary solvent and dispersive solvent amounts were determined using an experimental design. The main effects of these parameters and their interaction effects were assessed using analysis of variance. The detection limits of the analytes under optimal experimental conditions ranged between 0.16-1.5ng/mL. All analytes exhibited good linearity over broad calibration ranges, and high precision (%RSD<8.0%) was obtained for six repeated readings of the lowest concentrations of the calibration plots. The method's applicability and accuracy were tested on two municipal wastewater samples spiked at 10, 50, and 100ng/mL. The recovery results obtained ranged between 82 and 108%, indicating that the method can be used to quantify the analytes in wastewater matrix with substantial accuracy. In addition, matrix matching calibration method was used to improve the percent recovery (approximate to 100%) for a waste sludge sample spiked at 50ng/mL.
Keywords: Endocrine disruptors; Pesticides; Experimental design; Dispersive liquid-liquid microextraction; LIQUID-LIQUID MICROEXTRACTION; POLLUTANTS; Environmental Sciences & Ecology; Meteorology & Atmospheric Sciences; Water Resources